PENGARUH HARGA MINYAK DUNIA, HARGA EMAS DUNIA, DOW JONES INDUSTRIAL AVERAGE DAN INFLASI TERHADAP INDEX SAHAM SYARIAH (STUDI EMPIRIS DI NEGARA INDONESIA, MALAYSIA DAN UNI EMIRAT ARAB) - Ivahzada Marella Edgina, SE., M.ESy. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
: Capital markets have an important role for the economy of a country because of the stock market performed two functions: first as a means of funding for business or as a means for companies to obtain funds from investors. Fluctuations in the capital market will be associated with changes in various macroeconomic indicators. This study attempts to analyze the influence of world gold prices, oil prices, Dow Jones, and inflation. And also to analyze the differences retun of each index. Thee main indexes will be analyzed namely Jakarta Islamic Index, FTSE Bursa Malaysia Hijrah Shariah and FTSE NASDAQ Dubai 10 Shariah. This study uses monthly data from January 2011 to December 2014 from the three countries. The results showed that simultaneous world gold prices, oil prices, Dow Jones and inflation significantly influence the Jakarta Islamic Index, the FTSE Bursa Malaysia Hijrah Shariah and the FTSE NASDAQ Dubai 10 Shariah.